Problematika Kewenangan dan Kebijakan antara Badan Pengusahaan Batam dengan Ex Officio Wali Kota Batam - Emy Hajar Abra (University of Udayana, 2024)
The Batam Concession Agency/BP is a real form of centralization that occurs in the Batam City government. This can be seen from the various authorities and assets in Batam City. This is the impact of the Batam Free Trade Zone and Free Port Council Decree Number 1 of 2019. It is explained that the Head of BP Batam is the ex officio Mayor of Batam. The ex officio condition in Batam is when one person holds two authorities in two different institutions. This article aims to find out, analyze and identify problems related to authority and policy between the Batam Concession Agency and the ex officio Mayor of Batam. The research method in this paper is normative juridical, with secondary data, which is sourced from primary legal materials, namely binding legal materials, namely related laws and regulations. The results of the research in this paper are that there are various problems in the city of Batam due to the impact of the ex officio policy, including regulatory problems, authority problems in the Indonesian state administration. In theory, the regional government system does not recognize the centralization of authority from the center to the regions. This has a direct impact on the case of Rempang Island. This condition is not in line with Article 18 B paragraph (2) of the 1945 Constitution which states that the existence of customary law communities must be respected and maintained. In conclusion, it is necessary to reconstruct the regional government structure in Batam City which is consistent and coherent with the 1945 Constitution, like other regions. As for the Batam Business Agency, which is one of the investment supporting institutions, it is necessary to reorganize the position of this institution. Badan pengusahaan/ BP Batam adalah bentuk nyata sentralisasi yang terjadi dalam pemerintahan Kota Batam. Hal ini dapat dilihat dari berbagai kewenangan serta aset yang ada di Kota Batam. Hal tersebut adalah dampak dari adanya Keputusan Dewan Kawasan Perdagangan Bebas Dan Pelabuhan Bebas Batam Nomor 1 Tahun 2019. Dijelaskan bahwa Kepala BP Batam adalah ex officio Wali Kota Batam. Kondisi ex officio di batam adalah ketika satu orang memegang dua kewenangan pada dua lembaga yang berbeda. Tulisan ini bertujuan untuk mengetahui, menganalisis dan mengidentifikasi problematika kewenangan dan kebijakan antara Badan Pengusahaan Batam dan ex officio Wali Kota Batam. Metode penelitian dalam tulisan ini adalah yuridis normatif, dengan jenis data sekunder, yang bersumber pada bahan hukum primer yaitu bahan-bahan hukum yang mengikat yakni peraturan perundang-undangan terkait. Adapaun Hasil penelitian dalam tulisan ini adalah terdapat beragam problemtika dikota batam atas dampak dari kebijakan ex officio tersebut, diantaranya problemtika regulasi, problematika kewenangan dalam ketatanegaraan Indonesia pada teori system pemerintahan daerah tidak mengenal adanya sentralisasi kewenangan dari pusat ke daerah. Hal ini berdampak langsung pada contoh kasus pulau Rempang. Kondisi itu tidak sejalan dengan Pasal 18 B ayat (2) UUD 1945 bahwa kesatuan masyarakat hukum adat wajib dihormati dan dijaga keberadaannya. Kesimpulannya diperlukan rekonstruksi tatanan pemerintahan daerah pada Kota Batam yang konsisten dan koheren dengan UUD 1945 sebagaimana daerah-daerah lainnya. Adapun Badan Pengusahaan Batam yang menjadi salah satu lembaga penunjang investasi diperluakan penataan ulang pada kedudukan lembaga tersebut.